Penerapan Teknologi Sederhana Alat Pengebor Tanah untuk Mempermudah Penanaman Benih Tembakau pada Tanah Kering di Kecamatan Guluk-Guluk Sumenep Madura - Achmad Walid; Pipit Wahyu Nugroho; Santoso Santoso; Intan Fadhilah; Irwanda Yuni Pungkiarto; Khoirul Anwar (Pusat Riset dan Inovasi Nasional, 2025)
Guluk-guluk District is located on Madura Island, Sumenep Regency, East Java Province, and is known as the location of the long-established Annuqayah Islamic Boarding School. This district has a total rice field area of ​​approximately 1,141 hectares, and the majority of its population is engaged in farming. During the dry season, farmers in Guluk-guluk grow tobacco, which is an important trade commodity with high economic value for the local community. However, tobacco farmer groups in Guluk-guluk District face several serious challenges during the dry season. Lack of rainfall causes the soil in tobacco fields to become very hard, making it difficult for farmers to plant tobacco seeds efficiently. Currently, farmers are forced to use traditional tools such as crowbars to dig holes in the hard soil. This process is time-consuming and requires significant labor, reducing production efficiency and increasing farmers' workload. This situation makes it increasingly difficult for farmers to increase their agricultural yields. Therefore, through the Community Service program, the community service team aims to introduce simple technology in the form of soil drilling tools. This tool is designed to simplify the process of planting tobacco seeds in hard, dry soil and increase farmer efficiency. By using this efficient soil drill, it is hoped that the productivity of tobacco farmers in Guluk-guluk will increase. This tool not only speeds up the planting process but also reduces labor requirements, allowing farmers to focus more on other aspects of their farming. This program is expected to have a positive impact on improving farmer welfare and optimizing agricultural yields in Guluk-guluk District. Furthermore, the implementation of this technology is also expected to provide training and skills development for farmers in Guluk-guluk.